Avoiding adult in-hospital cardiac arrest: A retrospective cohort study to determine preventability. Issue 4 (July 2018) - Bingham, Gordon; Bilgrami, Irma; Sandford, Mandy; Larwill, Sarah; Orosz, Judit; Luckhoff, Carl; Kambourakis, Tony
Abstract: Introduction: This study had three main aims. Develop a methodology for reviewing in-hospital cardiac arrests (IHCA). Assess appropriateness and potential preventability of IHCAs. Identify areas for improvement within the rapid response system (RRS). Design: A retrospective cohort study of IHCA identified from an existing organisational electronic database of medical emergency (MET) and Code Blue team activation. Potential preventability of IHCA and Code Blue team activation were established by an expert panel based on a standardised case review process with descriptive and content analyses for each IHCA event. Setting: A university affiliated tertiary referral hospital with an established two-tier RRS in Melbourne, Australia. Participants: Same day and multi-day stay patients identified from an existing database as having an IHCA defined as attempted resuscitation with chest compressions, defibrillation, or both from January 2014 to December 2015. Main outcome measures: Outcome measures were: number of Code Blue activations; potential preventability of Code Blue activations and potential preventability of the IHCA event. Results: A total of 120 IHCA events equating to 0.58 per 1000 total admissions occurred. 11 (9%) of IHCA were determined to be potentially preventable due to a failure to escalate, medication errors and inappropriate management. 39 (33%) of 120 Code Blue team activations were determined to be potentially preventable. These were typically due to lack of identification and documentation for end of life (EOL) care in 16 (62%) cases and inappropriate resuscitation when limitations of care were already in place in 10 (38%) cases. Conclusions: The study centre has a comparably low rate of preventable IHCA which could be reduced further through improvements in documentation and handover process. A focus on improved communication, recognition and earlier instigation of appropriate EOL care will reduce this rate further.